Composite material and method for producing the same

A composite material with enhanced non-combustibility and mechanical strength is achieved by using a base material with dehydration-controlled reactions and aluminum cement, along with inorganic fibers, addressing the limitations of existing FRP materials.

JP7626473B2Active Publication Date: 2025-02-04EACH DREAM CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
JP2022541102
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2020-08-03
Filing Date
2020-09-18
Publication Date
2025-02-04
Estimated Expiration
2040-09-18

AI Technical Summary

Technical Problem

Existing composite materials, such as FRP, are not sufficiently non-combustible and do not provide the desired mechanical strength and heat resistance for applications like railway vehicles, ships, and water facilities.

Method used

A composite material is produced by incorporating a base material containing dehydration-controlled reactions and aluminum cement, with a higher proportion of sodium silicate and inorganic fibers like glass or basalt fibers, and a manufacturing process involving heating and laminating these components to enhance non-combustibility and mechanical strength.

Benefits of technology

The resulting composite material exhibits improved non-combustibility, mechanical strength, and heat resistance, with reduced smoke and odor generation, making it suitable for demanding applications.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

A composite material comprising a base material and an inorganic fiber, wherein the base material includes (a) a dehydration condensation reaction product of sodium silicate and (b) alumina cement. A method for producing a composite material comprising a base material and inorganic fiber, wherein the inorganic fiber is impregnated with a solution containing (A) sodium silicate and (B) alumina cement, and then heated to cause a dehydration condensation reaction of the component (A).
Need to check novelty before this filing date? Find Prior Art

Description

CROSS-REFERENCE TO RELATED APPLICATIONS

[0001] This international application claims priority based on Japanese Patent Application No. 2020-131656, filed with the Japan Patent Office on August 3, 2020, the entire contents of which are incorporated herein by reference. [Technical Field]

[0002] The present disclosure relates to composite materials and methods for making composite materials. [Background technology]

[0003] Fiber-reinforced plastics (FRP) have traditionally been used in the fields of railway vehicles, ships, and water facilities. FRP is a composite material containing a resin matrix and reinforcing fibers. Technology related to FRP is disclosed in Patent Document 1. [Prior art documents] [Patent documents]

[0004] [Patent Document 1] Japanese Patent Application Laid-Open No. 2000-318071 Summary of the Invention [Problem to be solved by the invention]

[0005] There is a demand for composite materials that are more non-combustible than FRP. In one aspect of the present disclosure, it is preferable to provide a highly non-combustible composite material and a method for producing the composite material. [Means for solving the problem]

[0006] One aspect of the present disclosure is a composite material including a matrix and inorganic fibers. The matrix includes (a) a dehydration condensation reaction product of sodium silicate and (b) alumina cement. The composite material according to one aspect of the present disclosure is highly non-flammable.

[0007] Another aspect of the present disclosure is a method for producing a composite material including a matrix and inorganic fibers. In this method, the inorganic fibers are impregnated with a solution containing (A) sodium silicate and (B) alumina cement, and the solution is heated to cause a dehydration condensation reaction in component (A). This method for producing a composite material, another aspect of the present disclosure, allows the production of a highly non-flammable composite material. DETAILED DESCRIPTION OF THE INVENTION

[0008] Exemplary embodiments of the present disclosure will now be described.

[0009] 1. Composition of composite materials The composite material of the present disclosure includes a matrix and inorganic fibers, e.g., the matrix is ​​impregnated with inorganic fibers, and the composite material is reinforced by the inorganic fibers.

[0010] The base material contains (a) a dehydration condensation reaction product of sodium silicate and (b) alumina cement. Component (a) is a product produced by a dehydration condensation reaction of sodium silicate. Component (a) is, for example, a compound having a skeleton with linked siloxane bonds. Component (a) includes, for example, siloxane. 100 parts by mass of sodium silicate becomes 60 parts by mass of component (a) as a result of the dehydration condensation reaction.

[0011] The mass of component (a) contained in the matrix is ​​preferably greater than the mass of component (b) contained in the matrix. When the mass of component (a) is greater than the mass of component (b), the non-combustibility and strength of the composite material are higher.

[0012] The base material preferably contains 5 to 25 parts by mass of component (b) per 100 parts by mass of component (a). When the amount of component (b) in the base material is within the above range, the strength of the composite material is even higher.

[0013] The base material may further contain other components, such as shirasu balloons and silicate minerals, and wollastonite, for example.

[0014] The base material preferably contains 5 to 20 parts by mass of shirasu balloons per 100 parts by mass of component (a). When the amount of shirasu balloons in the base material is within the above range, the composite material becomes even lighter.

[0015] The matrix preferably contains 5 to 15 parts by mass of silicate mineral per 100 parts by mass of component (a). When the amount of silicate mineral in the matrix is ​​within the above range, the composite material has higher heat resistance.

[0016] Examples of inorganic fibers include glass fiber and basalt fiber. The inorganic fiber is preferably in the form of a cloth. Examples of inorganic fibers include glass cloth made of glass fiber and glass cloth made of basalt fiber. When glass fiber or basalt fiber is used as the inorganic fiber, the composite material has higher non-flammability than when aluminum fiber or alumina fiber is used. When basalt fiber is used as the inorganic fiber, the composite material has higher mechanical strength. The reason for the high mechanical strength is presumed to be that basalt fiber is less susceptible to corrosion even when the base material is alkaline.

[0017] It is preferable that the inorganic fibers do not contain a binder made of an organic material. When the inorganic fibers do not contain a binder made of an organic material, the composite material is less likely to emit smoke or unpleasant odors even when heated to a temperature of 200°C or higher.

[0018] 2. Manufacturing method of composite materials The composite material of the present disclosure can be produced, for example, by a method essentially similar to that of conventional FRP production methods. However, whereas conventional FRP production methods use a liquid resin composition, the composite material production method of the present disclosure uses a solution containing (A) sodium silicate and (B) alumina cement (hereinafter referred to as a matrix solution).

[0019] The mass of component (A) contained in the base material solution is preferably greater than the mass of component (B) contained in the base material solution. When the mass of component (A) is greater than the mass of component (B), the non-combustibility of the produced composite material is even higher.

[0020] The base material solution preferably contains 5 to 50 parts by mass of component (B) per 100 parts by mass of component (A). When the amount of component (B) in the base material solution is within the above range, the strength of the produced composite material is even higher.

[0021] The base material solution may further contain other components, such as shirasu balloons and silicate minerals. Examples of silicate minerals include wollastonite.

[0022] The base material solution preferably contains 5 to 20 parts by mass of shirasu balloons per 100 parts by mass of component (A). When the amount of shirasu balloons in the base material solution is within the above range, the composite material becomes even lighter.

[0023] The matrix solution preferably contains 5 to 15 parts by mass of silicate mineral per 100 parts by mass of component (A). When the amount of silicate mineral in the matrix solution is within the above range, the heat resistance of the composite material is even higher.

[0024] An example of a method for producing a composite material is a production method (hereinafter referred to as a first production method) including the following steps (1) to (4).

[0025] (1) Formation of laminate (i) The base material solution is evenly applied to the inner surface of the production mold.

[0026] (ii) Place an inorganic fiber cloth on top of the area where the base material solution has been applied.

[0027] (iii) Using a mohair roller or the like, apply the base material solution to the inorganic fiber cloth.

[0028] (iv) Using a defoaming roller or the like, the base material solution is uniformly impregnated into the inorganic fiber mat while removing the air contained in the inorganic fiber cloth.

[0029] (v) Laminating a new inorganic fiber cloth.

[0030] (vi) The steps (iii) to (iv) are carried out on a new inorganic fiber cloth.

[0031] (vii) The steps (v) to (vi) are repeated until the number of laminated inorganic fiber cloths reaches a predetermined number. Through the steps above, a laminate is formed.

[0032] (2) Dry hardening The laminate, together with the production mold, is placed in a drying oven at 70-100°C for 5 hours. At this time, the solvent in the base material solution evaporates and the laminate hardens. Furthermore, (A) sodium silicate contained in the base material solution undergoes a dehydration condensation reaction to become component (a). Component (a) is a dehydration condensation reaction product of sodium silicate. (B) alumina cement contained in the base material solution functions as a hardening accelerator. As a result, the laminate becomes a composite material. The composite material includes a base material and inorganic fibers. The base material is impregnated with inorganic fibers. The composite material is reinforced by inorganic fibers. The base material includes component (a) and component (b).

[0033] (3) Demolding A gap is created between the production mold and the composite material using a spatula or similar tool. Air is blown into the gap using a compressor or similar tool. The composite material is then removed from the production mold. The composite material produced by the first manufacturing method is a molded product.

[0034] (4) Finishing work Unnecessary parts of the composite material are cut off using an electric sander or the like.

[0035] 3. Effects of composite materials The composite material of the present disclosure has higher fire resistance than conventional FRP, and also has high strength.

[0036] 4. Example 1 (4-1) Preparation of base material solution Base material solutions S1 to S3 having the following compositions were prepared: Base material solutions S1 to S3 were prepared by mixing the respective components.

[0037] (Base material solution S1) Sodium silicate JIS No. 3: 74.0 parts by mass Shirasu balloon: 7.4 parts by mass Silicate mineral (wollastonite): 7.4 parts by mass Alumina cement: 11.2 parts by mass (Base material solution S2) Sodium silicate JIS No. 3: 69.0 parts by mass Shirasu balloon: 6.9 parts by mass Silicate mineral (wollastonite): 6.9 parts by mass Alumina cement: 17.2 parts by mass (Base material solution S3) Sodium silicate JIS No. 3: 62.4 parts by mass Shirasu balloon: 6.3 parts by mass Silicate mineral (wollastonite): 6.3 parts by mass Alumina cement: 25.0 parts by mass (4-2) Manufacturing of composite materials A composite material was produced using base material solution S1 according to the first manufacturing method described above. A composite material was also produced using base material solution S2 according to the first manufacturing method described above. A composite material was also produced using base material solution S3 according to the first manufacturing method described above. Hereinafter, the composite materials produced using base material solutions S1, S2, and S3 will be referred to as composite materials S1, S2, and S3, respectively.

[0038] The inorganic fiber used in manufacturing composite materials S1 to S3 was glass cloth (manufactured by Nitto Boseki, product number: WF350-100-BS6). In composite materials S1 to S3, the number of layers of inorganic fiber cloth was 11. In the drying and hardening process, the temperature inside the drying oven was 100°C.

[0039] (4-3) Evaluation of composite materials The tensile strength of each of the composite materials S1 to S3 was measured by a tensile test in accordance with JIS K 7164. The tensile strength of the composite material S1 was 50.4 MPa.

[0040] A bending test was carried out on each of composite materials S1 to S3 to measure the bending strength and bending modulus in accordance with JIS K 7171. The bending strength of composite material S1 was 108.3 MPa. The bending modulus of composite material S1 was 4.430 GPa.

[0041] A heat generation test was conducted for each of the composite materials S1 to S3 in accordance with ISO-5660. In the heat generation test, the test specimen was heated for 20 minutes at a radiation intensity of 50 kW / m 2 It was.

[0042] In composite material S1, the total heat generation is 0.01 MJ / m 2 In composite material S1, the maximum heat generation rate was 0.33 kW / m 2 The heat generation test results showed that composite material S1 had a high non-flammability.

[0043] A non-combustibility test was conducted for each of the composite materials S1 to S3 in accordance with ISO-1182. The test method was as follows: A cylindrical electric furnace was prepared. A test specimen was also prepared. The shape of the test specimen was cylindrical, with a diameter of 44.6 mm and a height of 47.5 mm. The mass of the test specimen before the test was 125.46 g.

[0044] The temperature inside the electric furnace was adjusted to 750±5°C. After adjusting the furnace temperature, the electric furnace's power consumption was kept constant. After adjusting the furnace temperature, the test specimen was inserted into the furnace. After the test specimen was inserted, the furnace temperature, the core temperature of the test specimen, and the surface temperature of the test specimen were continuously measured. The mass of the test specimen was also measured before and after the test. The shape of the test specimen was also observed before and after the test. The test was continued until the furnace temperature reached the final equilibrium temperature. The final equilibrium temperature is the furnace temperature when the furnace temperature became stable within a range of ±2°C for 10 minutes.

[0045] For composite S1, the furnace temperature rise at the center of the specimen was 2°C. The furnace temperature rise is the maximum furnace temperature minus the final equilibrium temperature. The maximum furnace temperature is the highest furnace temperature from the time the specimen was inserted to the end of the test.

[0046] For composite material S1, the furnace temperature rise at the surface of the test specimen was 2.8°C. For composite material S1, the mass reduction rate WR of the test specimen was 12.0%. The mass reduction rate WR is a value expressed by the following formula (1).

[0047] Formula (1) WR=((W1-W2) / W1)×100 In equation (1), W1 is the mass of the test specimen before the test, and W2 is the mass of the test specimen after the test.

[0048] For composite material S1, the furnace temperature rise at the center of the specimen and the furnace temperature rise at the surface of the specimen were smaller than the ISO-1182 standard of 20°C. Furthermore, for composite material S1, the mass loss rate (WR) was smaller than the ISO-1182 standard of 30%. Furthermore, for composite material S1, the shape of the specimen after the test did not change significantly compared to the shape of the specimen before the test. The results of the non-combustibility test indicate that composite material S1 has high non-combustibility.

[0049] 5. Example 2 (5-1) Preparation of base material solution A base material solution S4 having the following composition was prepared: The base material solution S4 was prepared by mixing the components.

[0050] (Base material solution S4) Sodium silicate JIS No. 3: 74.0 parts by mass Shirasu balloon: 7.4 parts by mass Silicate mineral (wollastonite): 7.4 parts by mass Alumina cement: 7.4 parts by mass (5-2) Manufacturing of composite materials A composite material was produced by the above-described first production method using the base material solution S4. Hereinafter, the composite material produced using the base material solution S4 will be referred to as composite material S4.

[0051] The inorganic fiber used in manufacturing composite material S4 was basalt fiber (manufactured by Alteplus, product number AC1919G 102). The number of layers of inorganic fiber was 11. During the drying and curing process, the temperature inside the drying oven was 100°C.

[0052] (5-3) Evaluation of composite materials The tensile strength of composite material S4 was measured by a tensile test in accordance with JIS K 7164. The tensile strength of composite material S4 was 34.1 MPa.

[0053] The composite material S4 was subjected to a bending test in accordance with JIS K 7171 to measure its bending strength and bending modulus. The composite material S4 had a bending strength of 57.1 MPa and a bending modulus of 20.8 GPa.

[0054] 6. Other Embodiments Although the embodiments of the present disclosure have been described above, the present disclosure is not limited to the above-described embodiments and can be implemented in various modified forms.

[0055] (6-1) Multiple functions possessed by one component in the above embodiments may be realized by multiple components, or one function possessed by one component may be realized by multiple components. Also, multiple functions possessed by multiple components may be realized by one component, or one function realized by multiple components may be realized by one component. Also, part of the configuration of the above embodiments may be omitted. Also, at least part of the configuration of the above embodiments may be added to or substituted for the configuration of another of the above embodiments.

[0056] (6-2) In addition to the composite material described above, the present disclosure can also be realized in various forms, such as a system including the composite material as a component.

Claims

1. A composite material including a base material and inorganic fibers, The base material includes (a) a dehydration condensation reaction product of sodium silicate, (b) an alumina cement, and (c) a silicate mineral; The base material is a composite material containing 5 parts by mass or more and 15 parts by mass or less of the (c) component per 100 parts by mass of the (a) component.

2. 2. The composite material of claim 1 , A composite material, wherein the mass of the component (a) contained in the base material is greater than the mass of the component (b) contained in the base material.

3. A method for producing a composite material including a base material and inorganic fibers, comprising the steps of: The inorganic fibers are impregnated with a solution containing (A) sodium silicate, (B) alumina cement, and (C) a silicate mineral; By heating, a dehydration condensation reaction is caused in the component (A), The solution contains 5 parts by mass or more and 15 parts by mass or less of the (C) component relative to 100 parts by mass of the (A) component.

4. A method for producing the composite material according to claim 3, comprising the steps of: A method for producing a composite material, wherein the mass of the component (A) contained in the solution is greater than the mass of the component (B) contained in the solution.

Citation Information

Patent Citations

  • Manufacture of water-repellant calcium silicate formed body

    JP1986251554A

  • Refractory heat insulating board

    JP1987246880A

  • Lightweight nonburned tile

    JP2000281424A

  • Frp material and its manufacture

    JP2000318071A

  • Fiber reinforced acid resistant concrete

    JP2003165763A